Looking at the Bright Side: The Motivation Value of Overconfidence - Si Chen; Hannah Schildberg-Hörisch (Institute of Labor Economics (IZA), 2018)
The motivation value of confidence postulates that individual effort provision is increasing in beliefs on one's own productivity. This relationship also holds for overconfident individuals who have exaggerated productivity beliefs (motivation value of overconfidence). We present first empirical evidence on the existence of a motivation value of absolute overconfidence that many microeconomic models build on. Moreover, we document that debiasing information increases the accuracy of productivity beliefs of overconfident individuals but comes at the cost of diminished effort provision – a result that is of obvious relevance for many contexts such as labor relations or learning at school. As a further conceptual contribution, we offer a novel strategy for identifying significant overconfidence at the individual level.
Keywords: C91; D91; 330; overconfidence; effort provision; laboratory experiment